2014
DOI: 10.3233/jpd-130312
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screening for the LRRK2 R1441C and G2019S Mutations in Parkinsonian Patients from Campania

Abstract: Background: PARK8 is the most common known mendelian form of Parkinson's Disease (PD). It is due to mutations in the leucine-rich repeat kinase 2 (LRRK2) gene and G2019S is considered the most frequent mutation in the Caucasian population, in particular in the Southern Europe and Mediterranean countries. Objective: We assessed the frequency of the G2019S and R1441C/H/G mutations in 513 (311 M and 202 F) unrelated PD patients from Campania, in Southern Italy. Methods: Three hundreds and thirty-six patients pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The MDSGene systematic review also suggested that LRRK2 carriers have a good response to l -DOPA, late age at onset and absence of atypical signs (Trinh et al , 2018). However, other studies have not confirmed these findings (Lesage et al , 2005; Haugarvoll et al , 2008; Healy et al , 2008; Alcalay et al , 2010 b ; Belarbi et al , 2010; Ben Sassi et al , 2012; Puschmann, 2013; De Rosa et al , 2014; Estanga et al , 2014).…”
Section: Discussionmentioning
confidence: 80%
“…The MDSGene systematic review also suggested that LRRK2 carriers have a good response to l -DOPA, late age at onset and absence of atypical signs (Trinh et al , 2018). However, other studies have not confirmed these findings (Lesage et al , 2005; Haugarvoll et al , 2008; Healy et al , 2008; Alcalay et al , 2010 b ; Belarbi et al , 2010; Ben Sassi et al , 2012; Puschmann, 2013; De Rosa et al , 2014; Estanga et al , 2014).…”
Section: Discussionmentioning
confidence: 80%
“…Conversely, p.G2019S is extremely rare in East Asia ( 17 ). The other known pathogenic LRRK2 variants are very rare, with the exception of p.R1441G and p.R1441C, which are founder mutations in Basque and south Italian ethnicities, respectively ( 19 , 20 ). The penetrance of the p.G2019S variant is incomplete and age-dependent, peaking at 42.5–74% at the age of ~80 years ( 17 , 21 ), but varies among different ethnicities ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these 2 domains, the G2019S (kinase subunit) and the R1441C (Roc domain) are the most frequent disease‐segregating mutations. Importantly, in southern Italy, the R1441C mutation is more frequent than the G2019S mutation . Recent evidence pointed out that LRRK2 acts directly at the secretory and endocytic molecular machinery.…”
mentioning
confidence: 99%